2010
DOI: 10.1002/smi.1354
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring stress tolerance and occurrences of upper respiratory illness in basketball players by means of psychometric tools and salivary biomarkers

Abstract: The aim of the study was to evaluate the possible relationships between stress tolerance, training load, banal infections and salivary parameters during 4 weeks of regular training in fifteen basketball players. The Daily Analysis of Life Demands for Athletes' questionnaire (sources and symptoms of stress) and the Wisconsin Upper Respiratory Symptom Survey were used on a weekly basis. Salivary cortisol and salivary immunoglobulin A (SIgA) were collected at the beginning (before) and after the study, and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
41
1
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 27 publications
9
41
1
20
Order By: Relevance
“…These results corroborate the findings of Moreira et al 18 in a research also conducted with basketball players. The authors reported correlations between the number of URTI episodes and "worse than normal" responses for both sources (r = 0.79) and symptoms of stress (r = 0.65) in the second week of the research.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…These results corroborate the findings of Moreira et al 18 in a research also conducted with basketball players. The authors reported correlations between the number of URTI episodes and "worse than normal" responses for both sources (r = 0.79) and symptoms of stress (r = 0.65) in the second week of the research.…”
supporting
confidence: 92%
“…Similarly, the findings of Moreira et al 18 in a 4-week study with basketball players during a competitive period showed that a decrease in ITL in the fourth week of the research provoke a decrease in "worse than normal" responses.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…O questionário foi respondido semanalmente, conforme os procedimentos adotados em outros estudos (MOREIRA et al, 2011;ROBSON-ANSLEY;BLANNIN;GLEESON, 2007). O questionário DALDA é dividido em duas partes (A e B), as quais dizem respeito às fontes e sintomas de estresse, respectivamente.…”
Section: Tolerância Ao Estresseunclassified
“…Nesse sentido, questionários e diários vêm sendo utilizados para determinar o efeito da carga de treinamento nas respostas comportamentais dos atletas (estados de humor, tolerância ao estresse, bem-estar, qualidade de recuperação, infecção do trato respiratório superior, entre outros). Muitos estudos têm utilizado esta abordagem em conjunto com a PSE da sessão, adotando instrumentos psicométricos, os quais provem boa utilidade e fácil aplicação (GOMES et al, 2013;MCLEAN et al, 2010;MOREIRA et al, 2011;NUNES et al, 2014).…”
Section: Introductionunclassified